Pengaruh metode talking stick terhadap motivasi belajar siswa pada mata pelajaran ilmu pengetahuan alam dan sosial (IPAS) kelas IV SDN 4 Tente - Nurul Sabilah, Afni; Irawan, Ady; Septian Haryati, Mila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of the talking stick method on learning motivation in the subject of natural and social sciences (IPAS) for fourth-grade students at SDN 4 Tente. This study employs a quantitative approach with an experimental design using a one group pretest-posttest design. The sample consistsof 21 students, and dat were collected using a student learning motivation questionnaire consisting of 20 statements. Data analysis was conducted through normalty tests and paired sample t-test using SPSS 26 for windows. The results indicate an increase in the average learning motivation score from 54,67 in the pretest to 76,67 in the posttest. The t-test results show significant values before and after the implementation of the talking stick method. Thus, the talking stick method has been proven to have an effect on enhancing students’ learning motivation. This method can serve as an effective alternative teaching strategy at the elementary school level, particularly in the subject of IPAS.